Darcy-Forchheimer flow with variable thermal conductivity and Cattaneo-Christov heat flux. Issue 8 (7th November 2016) - Hayat, T.; Muhammad, Taseer; Al-Mezal, Saleh; Liao, S.J.
Abstract : Purpose: The objectives of present communication are threefolds. First is to model and analyze the two-dimensional Darcy-Forchheimer flow of Maxwell fluid induced by a stretching surface. Temperature-dependent thermal conductivity is taken into account. Second is to examine the heat transfer process through non-classical flux by Cattaneo-Christov theory. Third is to derive convergent homotopic solutions for velocity and temperature distributions. The paper aims to discuss these issues. Design/methodology/approach: The resulting non-linear system is solved through the homotopy analysis method. Findings: An increment in Deborah number β causes a reduction in velocity field f ′( η ) while opposite behavior is observed for temperature field θ ( η ). Velocity field f ′( η ) and thickness of momentum boundary layer are decreased when the authors enhance the values of porosity parameter λ while opposite behavior is noticed for temperature profile θ ( η ). Temperature field θ ( η ) is inversely proportional to the thermal relaxation parameter γ. The numerical values of temperature gradient at the sheet − θ ′(0) are higher for larger values of thermal relaxation parameter γ. Originality/value: To the best of author's knowledge, no such consideration has been given in the literature yet.